Prototype design for wearable veins localization system using near infrared imaging technique - Meng, G.C. (Institute of Electrical and Electronics Engineers Inc., 2015)
Advance biomedical engineering technologies are continuously changing the medical practices to improve medical care of patients nowadays. In this paper, we describe the concept used to prototype a device for needle insertion navigation during intravenous catheterization process via Near Infrared (NIR) imaging technique. A vein locator prototype using the NIR imaging technique and augmented reality (AR) technology have been developed in this work which is meant to be used in the process of intravenous catheterization. The challenges faced during the development of this prototype included the calibration of composite images in the see-through display. In this prototype, the Vuzix STAR 1200XL eyewear system has been used as the head mounted display and the imaging video is input by IR CCD camera. Additional, We select the optimum illumination by using NIR LED with wavelength of 830nm and 850nm in prototying to obtain the best contrast NIR venous image for different types of skin tone. Â© 2015 IEEE.